UNDERSTANDING OF EARLY CHILDHOOD PARENTS ON PROTECTION OF CHILDREN’S RIGHTS IN COASTAL COMMUNITIES IN BUTON ISLANDS - Manan; La Jeti (Jurnal Cakrawala Ilmiah, 2022)
The purpose of this study was to obtain information about parents' understanding of the protection of children's rights in the Buton Islands. This type of research is descriptive qualitative with the subject of parents. The results of the study show that parents do not fully have knowledge about the protection of children's basic rights in terms of the Law of the Republic of Indonesia Number 35 of 2014. Parents still exploit children to get benefits, so that children do not get a proper education, social and emotional. In addition, the occurrence of physical violence in the form of discrimination and neglect. Children who are physically and mentally disabled often get rejected and isolated from their environment. This shows the low awareness of parents to the protection of children's rights which include: The right to get an early education, develop their interests and talents, communicate with the surrounding environment and have the right to get love from their parents. The rights of the child are the obligations of the family, society and the state as mandated by law.